Self-Employment in the Developing World - Gindling, T. H.; Newhouse, David (World Bank, Washington, DC, 2013)
This paper analyzes heterogeneity among the self-employed in 74 developing countries, representing two thirds of the population of the developing world. After profiling how worker characteristics vary by employment status, we classify self-employed workers outside of agriculture as “successful” or “unsuccessful” entrepreneurs, based on two measures of success: Whether the worker is an employer, and whether they reside in a non-poor household. Four main findings emerge. First, jobs exhibit a clear pecking order, with household welfare and worker education highest for employers, followed by wage and salaried employees, non-agricultural own-account workers, non-agricultural unpaid family workers, and finally agricultural workers. Second, a substantial minority of own-account workers reside in non-poor households, suggesting that their profits are often a secondary source of household income. Third, as per capita income increases, the structure of employment shifts rapidly, first out of agriculture into unsuccessful non-agricultural self-employment, and then mainly into non-agricultural wage employment. Finally, roughly one third of the unsuccessful entrepreneurs share similar characteristics with their successful counterparts, suggesting they have the potential to be successful but face constraints to growth. We conclude that although interventions such as access to credit can benefit a substantial portion of the self-employed, effectively targeting the minority of self-employed with higher growth potential is important, particularly in low-income contexts. The results also highlight the potential benefits of policies that facilitate shifts in the nature of work, first from agricultural labor into non-agricultural self-employment, and then into wage and salaried jobs.